Pengaruh tingkat bunga dan belanja pembangunan terhadap investasi swasta dan penyerapan tenaga kerja di kabupaten malinau - Erwin Simanjuntak (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
Research aimed Knowing and analyzing the effect of the interest rate for investment credit to private investment on employment in Malinau. The results of the study can be explained as follows: The interest rate investment loan significant effect on private investment in Malinau. Development expenditure not significant effect on private investment in Malinau. Development spending significant effect on employment in Malinau. Private investment was not significant effect on absorption labor in Malinau. The interest rate investment loan indirect effect through private investment on employment in Malinau. Development expenditure indirect effect through private investment on employment in Malinau. Development spending and dominant influence indirectly through private investment on employment in Malinau.